Study on the risk factors for colorectal polyp recurrence: a cross-sectional retrospective cohort study - Li, Fang; Lu, Mengge; Xu, Bo; Xiang, Zheng; Zhang, Yuan; Cao, Boran; Li, Xuewei; Wu, Yanan; Zheng, Rongrong; Cai, Qin; Shen, Jun; Xin, Pengfei; et al. (Frontiers in Medicine, 2025)
ObjectiveTo investigate the factors associated with the recurrence of colorectal polyps.MethodsData on polyp recurrence and related factors, including gender, age, BMI, family history, smoking history, alcohol consumption history, gallbladder disease history, food allergy, polyp size, number, and pathological classification, Helicobacter pylori (Hp) infection, parathyroid hormone, gastrin, and blood lipid levels, were collected as exposure factors. Polyp recurrence was used as the outcome measure. Logistic regression analysis was used to evaluate risk and protective factors for colorectal polyp recurrence. The diagnostic performance of the identified risk factor model was assessed using ROC curve analysis.ResultsAmong the 318 patients, 170 experienced polyp recurrence, while 148 did not. Logistic regression analysis revealed that gender (OR = 1.927, 95% CI = 1.134–3.276, P = 0.015), age60–80years (OR = 3.228, 95% CI = 1.846–5.647, P < 0.001), history of gallbladder disease (OR = 2.011, 95% CI = 1.147–3.523, P = 0.015), food allergy (OR = 2.246, 95% CI = 1.211–4.545, P = 0.012), pathological classification (OR = 5.023, 95% CI = 2.932–8.606, P < 0.001), and Hp infection (OR = 1.970, 95% CI = 1.171–3.312, P = 0.011) were positively associated with polyp recurrence. Conversely, polyp size (OR = 0.324, 95% CI = 0.127–0.827, P = 0.018) was negatively associated with recurrence. Logit(p) = −2.459 + 0.656 × Gender + 1.172 × Age 61–80 years + 0.698 × Gallbladder Disease + 0.853 × Food Allergy−1.127 × Polyp Size + 1.164 × Pathological Classification + 0.678 × Hp Infection. The risk prediction model can be used to predict post-surgical recurrence of colorectal polyps with a sensitivity of 0.88 and specificity of 0.56. The cutoff value for this odds prediction model is 0.44.ConclusionElderly (61–80 years old) male patients with adenomatous colorectal cancer and the history of Helicobacter pylori (Hp) infection, gallbladder disease and food allergy have higher odds to experience recurrence after surgical resection. On the contrary, those patients with a larger polyp size (≥2 cm) are less odds to experience recurrence. Patients with a risk prediction model value greater than or equal to 0.44 have increased odds to experience postoperative recurrence.